PKM Bimbingan Menyelesaikan Soal Tes Potensi Skolastik (TPS) dalam Mempersiapkan Siswa Mengikuti UTBK- SBMPTN - Hermina Disnawati; Yohanis Ndapa Deda; Farly O.Haning; Marchy Pallo (Jurnal Masyarakat Mengabdi Nusantara, 2022)
Community Services in Solving Scholastic Potential Test (TPS) for Preparing Students to Take UTBK-SBMPTN Having a Computer-Based Written Examination (UTBK) score is a mandatory requirement for prospective students who continue their studies at public universities through the SBMPTN. The Scholastic Potential Test (TPS) is one of the materials in UTBK that really needs to be taught to students before taking UTBK. This community service aims to increase students' knowledge and skills in solving TPS problems. This PKM activity involved 47 class XII students majoring in Science, Social Studies and Language at SMAN 1 Kefamenanu and LBKP U-Genius Kefamenanu. The training was held for 8 weeks, with 120 minutes per meeting every weeks. PKM results show that there was an increase in students' cognitive abilities in solving TPS questions. In the pre-test, the lowest score was 70 and the highest was 230 out of a maximum score of 250. The average student got a score of 125.7. At the time of the post test, the lowest score was 100 and the highest was 250 from the maximum score of 250. The average was 193.8. Thus there was an increase in the student's score on the TPS test material by around 64.8%.